Optimizing Rotavirus Vaccine Cost: A Dynamic Approach for Global Health and Environmental Sustainability - Dwivedi, Vinita; Khedlekar, Uttam Kumar (Journal of Applied Nonlinear Dynamics, 2026)
This study addresses the global threat of rotavirus, particularly its impact on infants and young children, and emphasizes the importance of integrating rotavirus vaccines into childhood immunization programs, as recommended by the WHO. It highlights the need for promotional efforts to raise awareness, coupled with efficient vaccine inventory management due to perishability, using preservation techniques and cold storage. The study also proposes green technology investments to reduce carbon emissions from vaccine deterioration, aligning with Sustainable Development Goals. Advanced optimization algorithms, such as Ant Colony, Modified Flower Pollination, Cuckoo Search, and Particle Swarm Optimization, are utilized to optimize pricing, preservation, green investments, and replenishment schedules. Numerical experiments demonstrate the effectiveness of these dynamic investment strategies, and sensitivity analysis provides valuable insights for decision-makers. The study concludes by highlighting the role of green technology in managing the social and environmental impacts of vaccine inventories, offering practical solutions and strategic insights for rotavirus disease response.